2017
DOI: 10.1253/circj.cj-16-1334
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Clinical Outcome After 2nd-Generation Cryoballoon-Based Pulmonary Vein Isolation for the Treatment of Paroxysmal and Persistent Atrial Fibrillation ― A 2-Center Experience ―

Abstract: CB2-based PVI resulted in a 60.2% single-procedure and a 78.6% multiple-procedure success rate after 3 years. Repeat procedures demonstrated a high rate of durable PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Although CB ablation could be an alternative strategy for catheter ablation of persistent AF, the reported single procedure outcome is limited as compared to paroxysmal AF. 15 All these data highlight the importance of a proximal CB position during the application. The proximal-seal technique was initially proposed by Su et al to avoid deep CB positioning.…”
Section: Preprocedural and Intraprocedural Predictors Of Pnimentioning
confidence: 86%
See 1 more Smart Citation
“…Although CB ablation could be an alternative strategy for catheter ablation of persistent AF, the reported single procedure outcome is limited as compared to paroxysmal AF. 15 All these data highlight the importance of a proximal CB position during the application. The proximal-seal technique was initially proposed by Su et al to avoid deep CB positioning.…”
Section: Preprocedural and Intraprocedural Predictors Of Pnimentioning
confidence: 86%
“…It is plausible that advanced atrial remodeling might be associated with a higher incidence of PNI. Although CB ablation could be an alternative strategy for catheter ablation of persistent AF, the reported single procedure outcome is limited as compared to paroxysmal AF . All these data highlight the importance of a proximal CB position during the application.…”
Section: Discussionmentioning
confidence: 99%
“…The second‐generation CB (Arctic Front Advance, Medtronic Inc., Minneapolis, MN, USA) (CB2) has several advantages over the first generation in terms of design, enabling better cooling properties, and larger lesion formation . Although there were several studies about 1‐year follow‐up results of CB2, few studies have reported its mid‐ and long‐term satisfactory efficacy like RF ablation . However, all those studies with extended follow‐up data included limited numbers of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Balloon-based ablation systems have been developed to possibly solve these limitations, reduce procedure time and increase the safety and efficacy of PVI. 2,3 The visually guided laser balloon ablation (VGLB) system (HeartLight, CardioFocus, Marlborough, MA, USA) is a balloon-based ablation system that utilizes laser energy for PVI. 4,5 The 1st-generation laser balloon (LB1) showed high…”
mentioning
confidence: 99%